Valgus inter-trochanteric osteotomy and fixation with double angle barrel plate and Richard screw for neglected fracture neck femur in young adults – A prospective clinico-radiological cohort study - Ravindra Mohan; Shailendra Singh; Arpit Singh; Deepak Kumar; Narendra Singh Kushwaha; Sajiv Kumar (Asian Journal of Medical Sciences, 2022)
Background: Saving natural head is the primary aim of management in delayed presented intracapsular fracture neck of femur, especially in young population. Anatomical reduction of these fractures is a difficult task. Rather more difficult is to decide the method of fixation which might require additive procedure(s) and one such method is valgus osteotomy and fixation devices which are technically demanding. Aims and Objectives: Our aim is to evaluate the practicality and validity of valgus osteotomy and fixation with Richard screw and double angle barrel plate in delayed presented (more than 3 weeks) fracture neck of femur in young adults. Materials and Methods: We treated 18 patients with mean age of 39 years who presented late with valgus inter-trochanteric osteotomy and fixed with Richard screw and double angle barrel plate. The cases were evaluated radiologically and clinically for Harris hip score, limb length discrepancy, union time, neck-shaft angle and complications such as avascular necrosis and implant cut through. Results: 15 out of 18 patients (83%) united in an average period of 15 weeks (12–28 weeks) clinically as well as radiologically. In more than 70% of patients, the average Harris hip score was “Excellent to Good” (Harris hip score >80). Pre-operative Pauwel’s angle has been corrected from 72.5 to 33. All the patients with united fracture were able to walk with full weight bearing, sit cross legged, squat, and perform SLR and do one-leg stance. Conclusion: Fixation with Richard screw and120° double angle barrel plate provides rigid bony fixation and restore the limb length after valgus inter-trochanteric osteotomy. Valgus inter-trochanteric osteotomy is an effective method to achieve union in neglected fracture neck of femur, as it facilitates added compression at fracture site and stable internal fixation.